Interaction and Network analysis in heritage organizations in Valledupar - Colombia - Cabrera Martínez, Alejandra; Vidal Ortega, Antonio (Empiria. Revista de metodología de ciencias sociales, 2024)
Introduction: Between 2017 and 2022, it was carried out research on the management of cultural heritage organizations in the Colombian Caribbean. Caught our attention the quantity and quality of cultural organizations built in Valledupar, Colombia, in comparison to larger cities, and with greater economic resources. Objective: In this study we attempt to identify the economic support ecosystem in the cultural heritage organizations of the city of Valledupar (Cesar, Colombia) and, based on in-depth interviews, formulate postulates about the forces that have facilitated the development of a rich and complex cultural ecosystem, despite the scarcity of resources. Methodology: Social network analysis ARS was used, based on the methodology of Organizational life stories. Results: the relationship dynamics of seven cultural heritage organizations are shown. The network of support that organizations use to survive were represented, which allow them to improve management and strengthen their relationship systems for financing, learning and access to new services and resources. The SNA methodology allowed us to identify the greatest supports, the type of networks, and the development possibilities of the organizations analyzed. Introducción: Entre 2017 y 2022 se realizó una investigación sobre la gestión de las organizaciones del patrimonio cultural en el Caribe colombiano. Nos llamó la atención la cantidad y calidad de las organizaciones culturales construidas en Valledupar, Colombia, en comparación con ciudades más grandes y con mayores recursos económicos. Objetivo: En este estudio intentamos identificar el ecosistema de soporte económico de las organizaciones patrimoniales culturales de la ciudad de Valledupar (Cesar, Colombia) y, a partir de entrevistas en profundidad, formular postulados sobre las fuerzas que han facilitado el desarrollo de un rica y complejo ecosistema cultural, a pesar de la escasez de recursos. Metodología: Se utilizó el análisis de redes sociales ARS, con base en la metodología de Historias de vida organizacionales. Resultados: Se muestra la dinámica de relación de siete organizaciones de patrimonio cultural. Se representaron las redes de apoyo que utilizan las organizaciones para sobrevivir, que les permiten mejorar la gestión y fortalecer sus sistemas de relacionamiento para el financiamiento, el aprendizaje y el acceso a nuevos servicios y recursos. La metodología ARS permitió identificar los mayores apoyos, el tipo de redes, los conflictos y las posibilidades de desarrollo de las organizaciones analizadas.